Search for W′ boson decaying to electron-neutrino pairs in pp̄ collisions at s=1.96TeV - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We present the results of a search for W′ boson decaying to electron-neutrino pairs in pp̄ collisions at a center-of-mass energy of 1.96 TeV, using a data sample corresponding to 205pb-1 of integrated luminosity collected by the CDF II detector at Fermilab. We observe no evidence for this decay mode and set limits on the production cross section times branching fraction, assuming the neutrinos from W′ boson decays to be light. If we assume the manifest left-right symmetric model, we exclude a W′ boson with mass less than 788GeV/c2 at the 95% confidence level. © 2007 The American Physical Society.